Revitalisasi Nila Kearifan Lokal (Duka Se Cinta) Sebagai Sumber Belajar IPS di SMP Negeri 13 Kota Ternate - Zulkifli, Zulkifli (Peneliti.net, 2023)
The aim of this research is to determine and analyze the role of social studies teachers in utilizing local wisdom values as a learning resource at SMP Negeri 13 Tenrate City, to revitalize the value of local wisdom